Comparative effects of transcatheter versus surgical pulmonary valve replacement: A systematic review and meta-analysis - Bunchai Chongmelaxme; Kok Pim Kua; Chanokpol Amornvetchayakul; Nichapond Chawviriyathep; Thunyapat Kerdklinhom (PLoS ONE, 2025)
Introduction Transcatheter pulmonary valve replacement (TPVR) is developed as a non-surgical, minimally invasive procedure to reduce the need for re-do cardiac surgical interventions. However, its impacts on patient outcomes are less clear. This study aims to investigate the effects of TPVR among patients with pulmonary valve or right ventricular outflow tract dysfunctions. Materials and methods In this systematic review and meta-analysis, we searched PubMed, Cochrane CENTRAL, EMBASE, CINAHL Complete, and Web of Science, from database inception to March 1, 2024, to identify studies that assessed the comparative effectiveness of transcatheter pulmonary valve replacement (TPVR) and surgical pulmonary valve replacement (SPVR). The key outcomes of interest included mortality, pulmonary regurgitation (PR), infective endocarditis (IE), re-intervention, improvements in cardiac failure based on the New York Heart Association (NYHA) functional classification, and adverse events. Meta-analyses using a random-effects model were performed. Results A total of 28 studies (n = 16,150) were included. The meta-analyses depicted that when compared with SPVR, TPVR reduced risks of mortality by 36% (odds ratio [OR] = 0.64 [95% confidence interval, CI: 0.43, 0.95]), but conferred a three-fold greater odd of IE over the follow-up duration (OR = 3.10 [95% CI: 2.22, 4.33]). No significant differences were observed for 30-day mortality, and the early PR, IE and re-intervention, as well as the PR and re-intervention during follow-up. Meta-analyzed results across the outcome measures varied according to geographical region, publication year cut-off, and income status of country. All patients who had undergone valve replacement showed improvements in heart function and experienced relevant post-procedural complications. Conclusions TPVR afforded significant clinical benefits in patient survival, but nonetheless, it was associated with an elevated risk for infective endocarditis.